Supplementary cementitious materials origin from agricultural wastes - A review - Aprianti, E.; Shafigh, P.; Bahri, S.; Farahani, J.N. (Elsevier, 2015)
Concrete is heavily used as a construction material in modern society. With the growth in urbanization and industrialization, the demand for concrete is increasing day by-days. Therefore, raw materials and natural resources are required in large quantities for concrete production worldwide. At the same time, a considerable quantity of agricultural waste and other types of solid material disposal are posing serious environmental issues. To minimize and reduce the negative impact of the concrete industry through the explosive usage of raw materials, the use of agricultural wastes as supplementary cementitious materials, the source of which are both reliable and suitable for alternative preventive solutions promotes the environmental sustainability of the industry. This paper reviews the possible use of agricultural wastes as a supplementary cementitious material in the production of concrete. It aims to exhibit the idea of utilizing these wastes by elaborating upon their engineering, physical and chemical properties. This provides a summary of the existing knowledge about the successful use of agricultural wastes such as rice husk ash, palm oil fuel ash, sugar cane bagasse ash, wood waste ash, bamboo leaf ash, and corn cob ash in the concrete industry. (C) 2014 Elsevier Ltd. All rights reserved.